Lanthanide-based downshifting layers tested in a solar car race - Correia, Sandra F. H. (2021)
The mismatch between the AM1.5G spectrum and the photovoltaic (PV) cells absorption is one of the most limiting factors for PV performance. To overcome this constraint through the enhancement of solar energy harvesting, luminescent downshifting (LDS) layers are very promising to shape the incident sunlight and, thus, we report here the use of Tb3+- and Eu3+-doped organic-inorganic hybrid materials as LDS layers on Si PV cells. Electrical measurements on the PV cell, done before and after the deposition of the LDS layers, confirm the positive effect of the coatings on the cell's performance in the UV spectral region. The maximum delivered power and the maximum absolute external quantum efficiency increased 14% and 27%, respectively. Moreover, a solar powered car race was organized in which the small vehicle containing the coated PV cells presented a relative increase of 9% in the velocity, when compared to that with the uncoated one.